EXPLORING STUDENTS’ PERSPECTIVES IN SPEAKING: TikTok as a Learning Tool for Sociology Students in Blitar - fuad sholikhi (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2025)
Since the Covid-19 pandemic, online teaching has evolved into a learning platform that is being studied.